L-Arginine Enhances Intracellular Killing of Carbapenem-Resistant Klebsiella pneumoniae ST258 by Murine Neutrophils - Peñaloza, Hernán F.; Ahn, Danielle; Schultz, Bárbara M.; Piña-Iturbe, Alejandro; González, Liliana A.; Bueno, Susan M. (Frontiers in Cellular and Infection Microbiology, 2020)
Carbapenem-resistant Klebsiella pneumoniae ST258 (CRKP-ST258) are a global concern due to its rapid dissemination, high lethality, antibiotic resistance and resistance to components of the immune response such as neutrophils. Neutrophils are major host mediators, protecting against well-studied and antibiotic-sensitive laboratory reference strains of K. pneumoniae. However, CRKP-ST258 are able to evade neutrophil phagocytic killing, persisting longer in the host despite a robust neutrophil recruitment. L-arginine metabolism has been identified as an important modulator of the host immune response and positively regulate T cells, macrophages and neutrophils in response to microbes. Despite the similar efficiency of phagocytosis by neutrophils of a prototypic K. pneumoniae ATCC 43816 (KPPR1) and a previously characterized CRKP-ST258 isolate (KP35), neutrophils infected with KP35 were unable to clear the bacteria and presented a defect in phagosome acidification. Importantly, we observed that L-arginine supplementation improved phagosome acidification and KP35 clearance by neutrophils. Our data show the ability of KP35 to dysregulate the intracellular microbiocidal machinery of neutrophils to survive in the intracellular environment. This process, however, can be reversed after L-arginine supplementation.